Early Diagnosis of Wilson’s Disease in Children in Southern China by Using Common Parameters - Zhou, Jianli; Zhang, Qiao; Zhao, Yuzhen; Chen, Moxian; Zhou, Shaoming; Cheng, Yongwei (Frontiers in Genetics, 2022)
Abstract Aims: Development of early diagnostic criteria for Wilson's disease (WD) in children by using ALT (alanine aminotransferase) elevation as the first symptom. Methods: A cross-sectional retrospective analysis of the clinical data and genetic test results of children with WD in southern China in the past four years, and the follow-up study of their short-term prognosis. Results: Thirty children with elevated ALT as the first manifestation of WD in southern China were enrolled in this study, including 14 females and 16 males. Among them, liver enzymes of 30 cases (100%) were found to be elevated in physical examination. Specifically, in all the 30 cases (100%), serum ceruloplasmin (CP) level was decreased, whereas the 24-hour urinary copper excretion volume was increased. The genetic mutation test of ATP7B gene is used to confirm the diagnosis. In particular, the two mutation sites c.2333G>T and c.3443T>C have the highest mutation frequency, accounting for 23.0% and 10.7% of the total number of mutation sites, respectively. Conclusions: Early diagnosis and treatment of WD will substantially increase the survival rate and have good prognosis. And this early diagnosis in children could be done quickly by referring to three parameters including elevated ALT, decreased ceruloplasmin level and increased 24-hour urinary copper. This diagnostic standard can be applied in routine physical examination, together with negative result from head MRI examination and no neurological manifestations.